Two revenue sharing contracts in a three-echelon supply chain with a risk-neutral or a risk-averse retailer - Yumei Hou; Fangfang Wei; Xin Tian; Xiaoyun Liu (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: This paper compares the efficiency of two revenue-sharing contracts and discusses the members' preference for a three-echelon supply chain with the retailer's different risk attitude. Design/methodology/approach: This paper focuses on a three-echelon supply chain with a manufacturer, a distributor and a retailer. If the retailer is risk-neutral, the coordination of the supply chain based on the two revenue-sharing contracts is comparatively studied. If the retailer is downside-risk-aversion, the supply chain performance is comparatively analyzed and a risk-sharing contract is designed to coordinate the supply chain. Finally, the two revenue-sharing contracts under the risk-sharing contract are still compared. Findings: Although both the two revenue-sharing contracts can coordinate the supply chain with a risk-neutral retailer, they are not always able to coordinate the supply chain with a risk-averse retailer. It is interesting that the supply chain with a risk-averse retailer can be coordinated by executing a designed risk-sharing contract, which is based on any kind of revenue-sharing contract. Finally, any kind of revenue-sharing contracts is not absolutely better than another. Based on the risk-sharing contract, the retailer's preference is equivalent between the two contracts; but for the distributor and the manufacturer, their preferences between the two contracts are positively related to their own profit share in the supply chain.
Keywords: 650; supply chain; three-echelon; revenue-sharing contract; risk-aversion